2014
DOI: 10.1097/sle.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Closed-tube Thoracostomy

Abstract: The new technique provides safe tube introduction and precise tube positioning, saves time, and involves no technical precautions. The technique has been applied on selected simple cases as the first trial and requires further testing in cases of hemothorax, empyema thoracis, traumatic chest injuries, and complicated pulmonary diseases that require drainage. Further evaluation of the technique by randomized studies is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Furthermore, Kuckelman et al showed that the Reactor™ was significantly more successful at achieving rapid and complete resolution of tension pneumothorax compared to needle decompression (88% vs. 44%, P < 0.001) in a post-mortem swine model. Laparoscopic-type trocar procedures have been reported in two human case series for the treatment of simple pneumothoraces in which a chest tube is subsequently inserted through the trocar [4, 5]. Nevertheless, tube thoracostomy using a trocar-type device or the Reactor™ has not yet been compared with the standard, open technique.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kuckelman et al showed that the Reactor™ was significantly more successful at achieving rapid and complete resolution of tension pneumothorax compared to needle decompression (88% vs. 44%, P < 0.001) in a post-mortem swine model. Laparoscopic-type trocar procedures have been reported in two human case series for the treatment of simple pneumothoraces in which a chest tube is subsequently inserted through the trocar [4, 5]. Nevertheless, tube thoracostomy using a trocar-type device or the Reactor™ has not yet been compared with the standard, open technique.…”
Section: Discussionmentioning
confidence: 99%